2003
DOI: 10.1111/j.1432-2277.2003.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

The safety of the donor operation in living-donor liver transplantation: an analysis of 45 donors

Abstract: We retrospectively assessed the safety of the donor operation, based on parameters such as blood loss, blood transfusion, operation time, duration of hospitalization, and complications. Forty-five pediatric and adult recipients underwent living-donor liver transplantation (LDLTx) in Tohoku University Hospital from July 1991 to October 2000. Donor operations were classified into three groups. In the LS group, the graft was the lateral segment (n=20); in the LL group, the graft was the left lobe without the midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…Other studies have reported different findings from our results on postoperative LFT, blood loss and transfusion, and duration of hospital stay according to the type of donor hepatectomy [8–11]. Sugawara et al [10] reported that although the longest surgical time and the greatest blood loss were observed in LL compared with LSS and RL, duration of postoperative hospital stay and blood transfusion units showed no differences among the three groups.…”
Section: Discussioncontrasting
confidence: 91%
“…Other studies have reported different findings from our results on postoperative LFT, blood loss and transfusion, and duration of hospital stay according to the type of donor hepatectomy [8–11]. Sugawara et al [10] reported that although the longest surgical time and the greatest blood loss were observed in LL compared with LSS and RL, duration of postoperative hospital stay and blood transfusion units showed no differences among the three groups.…”
Section: Discussioncontrasting
confidence: 91%
“…Considering the second critical outcome, the liver dysfunction tests were reported in 13 studies, 18 , 23 25 , 33 , 44 , 52 , 58 , 67 , 69 , 71 73 50–50 criteria 76 were used only in two studies 20 , 24 . The bilirubin and INR (the perioperative peak and at 5 days) values were significantly lower ( p < .001) in patients undergoing left lobe compared to patients with right lobe hepatectomy 68 .…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies 19 , 22 , 24 , 25 , 27 , 30 , 38 , 40 , 42 , 43 , 45 , 47 , 52 were European, 11 23 , 24 , 29 , 32 , 37 , 41 , 53 , 56 , 57 , 63 , 66 American (North and south), 28 20 , 21 , 24 , 26 , 28 , 31 , 33 , 34 36 , 44 , 46 , 48 51 , 54 , 55 , 60 , 62 , 64 , 65 , 67 69 , 71 73 were Asian‐Pacific, and 5 18 , 39 , 58 , 59 , 70 were African. Of the studies selected, 29 were published before 2011, 18 , 19 , 21 , 22 , 26 , 27 , 29 32 , 34 , 38 42 , 48 51 , 53 55 , 57 ,...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations